Under-reporting Tuberculosis Cases At Private Health Sector: A Scoping Review - Suryanti, Suryanti; Ahmed, Idris Adewale (Journal of health research and technology, 2024)
Tuberculosis (TB) remains a formidable threat to human civilization, with several factors contributing to its increasing burden. Challenges such as inconsistent case finding and diagnosis procedures, inadequate reporting, under diagnosing, unreliable drug supply, and substandard monitoring and recording practices collectively exacerbate the problems associated with TB. A major hurdle in effective TB control, especially in high-incidence countries where the private sector is heavily involved, is the significant underreporting of cases. To learn more about under reporting at private health sector, we conducted this scoping review. We screening articles related to under reporting at private health sector in PubMed, Google Scholars, and Science Direct electronic database. We included 36 studies of 95 screened records, of which observational (26), experimental (9), and qualitative (4) studies. Under reporting is influenced by various factors, including patient characteristics (such as being male, pediatric, or over 65 years old), health worker’s issues (unqualified or overworked personnel, staff shortages, lack of awareness, and insufficient incentives), and health systems (poor supervision, accountability, and a lack of support for hospital notification systems or complex health information management systems). Addressing these multifaceted issues is crucial for improving TB control efforts worldwide.